Дискретизация плоской задачи о растяжении тела с трещиной при нелинейном законе деформирования - Хорошун, Л.П. (Прикладная механика, 2010)
A plane problem on tension of a body with crack with piece-wise diagram of
deformation is reduced by the Fourier-transform method to the system of nonlinear algebraic
equations. The body contains a crack. Basing on numerical solution of the system for
the plane strain and stress state of perfect elasto-plastic material, the plastic strain zones,
stresses and strains distribution, displacements of crack sides are studied. Плоска задача про розтяг тіла з тріщиною при кусково-лінійній діаграмі деформування зведена методом Фур’є-перетворення до системи нелінійних алгебраїчних рівнянь. На основі чисельного розв’язання системи для плоских деформівного і напруженого станів ідеального пружно-пластичного матеріалу досліджено зони пластичних деформацій, розподіл напружень і деформацій, переміщення берега тріщини.